Glycoside Hydrolases and Non-Enzymatic Glycation Inhibitory Potential of Viburnum opulus L. Fruit-In Vitro Studies - Dominika Kajszczak; Agnieszka Kowalska-Baron; Anna Podsędek (MDPI AG, 2021)
Phytochemicals of various origins are of great interest for their antidiabetic potential. In the present study, the inhibitory effects against carbohydrate digestive enzymes and non-enzymatic glycation, antioxidant capacity, and phenolic compounds composition of Viburnum opulus L. fruits have been studied. Crude extract (CE), purified extract (PE), and ethyl acetate (PEAF) and water (PEWF) fractions of PE were used in enzymatic assays to evaluate their inhibitory potential against α-amylase with potato and rice starch as substrate, α-glucosidase using maltose and sucrose as substrate, the antioxidant capacity (ABTS, ORAC and FRAP assays), antiglycation (BSA-fructose and BSA-glucose model) properties. Among four tested samples, PEAF not only had the highest content of total phenolics, but also possessed the strongest α-glucosidase inhibition, antiglycation and antioxidant activities. UPLC analysis revealed that this fraction contained mainly chlorogenic acid, proanthocyanidin oligomers and flavalignans. Contrary, the anti-amylase activity of V. opulus fruits probably occurs due to the presence of proanthocyanidin polymers and chlorogenic acids, especially dicaffeoylquinic acids present in PEWF. All V. opulus samples have an uncompetitive and mixed type inhibition against α-amylase and α-glucosidase, respectively. Considering strong anti-glucosidase, antioxidant and antiglycation activities, V. opulus fruits may find promising applications in nutraceuticals and functional foods with antidiabetic activity.